Development of a Contractile Cardiac Fiber From Pluripotent Stem Cell Derived Cardiomyocytes - Hansen, Katrina J.; Laflamme, Michael A.; Gaudette, Glenn R. (Frontiers in Cardiovascular Medicine, 2018)
Stem cell therapy has the potential to regenerate cardiac function after myocardial infarction. In this study, we sought to examine if fibrin microthread technology could be leveraged to develop a contractile fiber from human pluripotent stem cell derived cardiomyocytes (hPS-CM). hPS-CM seeded onto fibrin microthreads were able to adhere to the microthread and began to contract seven days after initial seeding. A digital speckle tracking algorithm was applied to high speed video data (>60fps) to determine contraction behaviour including beat frequency, average and maximum contractile strain, and the principal angle of contraction of hPS-CM contracting on the microthreads over 21 days. At day 7, cells seeded on tissue culture plastic beat at 0.83±0.25beats/sec with an average contractile strain of 4.23±0.23%, which was significantly different from a beat frequency of 1.11±0.45beats/sec and an average contractile strain of 3.08±0.19% at day 21 (n=18, p<0.05). hPS-CM seeded on microthreads beat at 0.84±0.15beats/sec with an average contractile strain of 3.56±0.22%, which significantly increased to 1.03±0.19beats/sec and 4.47±0.29%, respectively, at 21 days (n=18, p<0.05). At day 7, 27% of the cells had a principle angle of contraction within 20 degrees of the microthread, whereas at day 21, 65% of hPS-CM were contracting within 20 degrees of the microthread (n=17). Utilizing high speed calcium transient data (>300fps) of Fluo-4AM loaded hPS-CM seeded microthreads, conduction velocities significantly increased from 3.69±1.76cm/s at day 7 to 24.26±8.42cm/s at day 21 (n=5-6, p<0.05). hPS-CM seeded microthreads exhibited positive expression for connexin 43, a gap junction protein, between cells. These data suggest that the fibrin microthread is a suitable scaffold for hPS-CM attachment and contraction. In addition, extended culture allows cells to contract in the direction of the thread, suggesting alignment of the cells in the microthread direction.